Morphological Characteristics of Fetal Muscles: Gemellus Superior, Gemellus Inferior and Obturatorius Internus - Kołaczkowski, Zdzisław; Posłuszny, Mariusz (Anthropological Review, 1981)
The structure and degree of development of the three muscles (gemellus superior, gemellus inferior, obturatorius internus) were observed in 31 male and 19 female human fetuses. Crown-rump length of these fetuses ranged from 149 - 360 mm, i.e., the approximate age of fetuses was 17th to 40th week. Results concerning the structure and localization of muscles are illustrated by selected photographs.